đặt \(A=\frac{2^{2015}+1}{2^{2012}+1}\); \(B=\frac{2^{2017}+1}{2^{2014}+1}\)
ta có :\(A=\frac{2^{2015}+1}{2^{2012}+1}\)
\(\frac{1}{2^3}A=\frac{2^{2015}+1}{2^{2015}+8}=\frac{2^{2015}+8-7}{2^{2015}+8}=1-\frac{7}{2^{2015}+8}\)
\(B=\frac{2^{2017}+1}{2^{2014}+1}\)
\(\frac{1}{2^3}B=\frac{2^{2017}+1}{2^{2017}+8}=\frac{2^{2017}+8-7}{2^{2017}+8}=1-\frac{7}{2^{2017}+8}\)
vì 22015 + 8 < 22017 + 8 nên \(\frac{7}{2^{2015}+8}>\frac{7}{2^{2015}+8}\)
\(\Rightarrow1-\frac{7}{2^{2015}+8}< 1-\frac{7}{2^{2017}+8}\)
hay \(\frac{1}{2^3}A< \frac{1}{2^3}B\)
\(\Rightarrow A< B\)